EVALUATION OF THE ISOKINETIC TRUNK MUSCLE STRENGTHS' OF OPERATED LOMBER DISCOPATHY AND HEALTHY SUBJECTS AND THE FACTORS INFLUENCING MUSCLE STRENGTH - Cevriye Karaca,; Ece Aydoğ,; Ajda Bal,; Ece Ünlü,; Aytül Çakçı, (Archives of Rheumatology, 2005)
Objectives: The primary aim of this study is to compare the isokinetic trunk muscle strength of subjects who had been operated due to lomber disc hernia (LDH) and healthy subjects. The secondary objective is to investigate the effects of age, sex, height, weight, Body Mass Index (BMI), spinal mobility, pain and disability on the isokinetic trunk muscle strength of the operated LDH patients. Methods: Fifty five subjects (30 males, 25 females) who had been operated due to LDH and who have no difference of age, height, weight, BMI, and having similar smoking, alcohol and exercise habits were compared with a healthy control group of 20 subjects (11 males, 9 females). For the purpose of evaluating the lomber spinal mobility, modified Schober test (MST) and finger-to-floor distance (FFD) were measured for the operated subjects. For the low back-leg pain, VAS (0-10 cm) and for the functionality, Oswestry Disability Questionnaire (ODQ) were performed. For all the operated and healthy subjects the trunk flexor and extensor muscle strengths were measured at semi standing position using the isokinetic system (Biodex Medical Systems, Shirley, NY) at 60 o, 90 o and 120 o /sec speeds. Results: For the operated subjects, at 60o /sec and 120o /sec, statistically significant decreases in the extension peak torque/body weight (PT/BW) values were found. On the other hand, only at 60 o /sec speed, statistically significant higher values of F/E peak torque ratios were observed (p<0.05). It was also found that a statistically significant correlation exists between the trunk muscle strengths of the operated subjects and the independent variables such as MST, BMI, height, sex and smoking habits. A multiple regression analysis showed that for these patients trunk muscle strength are affected by MST, BMI and height. Conclusions: The trunk muscle strengths of the subjects operated for lomber discopathy are weak and this weakness is more emphasized for the extensor muscles. Spinal mobility and BMI are important factors on the muscle strength.